Evaluasi EVALUASI PENERAPAN METODE 5R+S (Ringkas,Rapi,Resik,Rawat,Rajin + Safety) PADA RUANG PRODUKSI UNTUK MENINGKATKAN PRODUKTIVITAS DI CV. UNICORN KENCANA INDOPETRA - Ahmad Miftaqul Aqyar; Indro Kirono (AkMen JURNAL ILMIAH, 2023)
The purpose of this observation is to evaluate the implementation of the 5R+S method in the production room in an effort to uphold productivity in CV. Unicorn Kencana Indopetra. High productivity is the company's main factor in facing intense global competition. The 5R+S method is an approach that follows five steps regarding concise, neat, clean, maintain, diligent, and safety. With the aim of creating an orderly and efficient work environment. Research was conducted through evaluation of the application of the 5R+S method in the company's production space. Data collection goes through hands-on processing,interviews,and analysis of related data. The evaluation results show that the company has implemented a 5R culture and K3 (Occupational Safety and Health) regulations for its employees and workers. However, there are still obstacles in implementing this method, especially related to the lack of awareness and discipline of workers in following the 5R procedure. Through careful evaluation, the company can identify the successes that have been achieved and the obstacles that may arise during the application of this method. Therefore, suggestions given from this study for improvement, including increased employee awareness and training, increased supervision, reward and recognition, evaluation and continuous improvement, and employee collaboration and active participation.